GROWTH AND BLOW-UP OF SOLUTIONS WITH POSITIVE INITIAL ENERGY FOR A VISCOELASTIC KIRCHHOFF EQUATION WITH A LOGARITHMIC NONLINEARITY, DELAY AND BALAKRISHNAN-TAYLOR DAMPING TERMS - Choucha A.; Jan R.; Mekawy I.; Alharbi A.; Alnegga M. (American Institute of Mathematical Sciences, 2025)
A nonlinear viscoelastic Kirchhoff-type equation with a logarithmic nonlinearity, delay and Balakrishnan-Taylor damping terms is studied. We prove the exponential growth and the blow-up of solutions with positive initial-energy under suitable hypotheses. ? 2024 American Institute of Mathematical Sciences. All rights reserved.